Proper Implementation of the Exhaustion Theory for Increasing Benefit of Parallel Imports - Reggiannie Christy Natalia (Universitas Pelita Harapan, 2017)
Parallel import has been an important issue in international trade. Business people have been buying genuine products from one country and selling them to another country that offers a higher price without the permission of the intellectual property owner. This practice is not always illegal because it is protected by the laws of some countries and it depends on the types of exhaustion theory that they have applied in their national law. This study will mainly discuss the various types of exhaution theory, how the theory effects parallel imports, and the application of the theory by the EU, WTO and WIPO. Therefore, by examining the indicated areas, this study aims to find the proper implementation of exhaustion theory and thus to provide appropriate recommendations for the practice.